KEPEMILIKAN MANAJERIAL MEMODERASI HUBUNGAN ANTARA INTERNAL GOVERNANCE, ASIMETRI INFORMASI, DAN FREE CASH FLOW TERHADAP REAL EARNINGS MANAGEMENT: (STUDI EMPIRIS PADA PERUSAHAAN CONSUMER NON-CYCLICALS YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2024) - Hilda Sri Hastuti Hilda; Nofryanti Nofryanti; Iin Rosini (Politeknik Ganesha Medan, 2026)
This study aims to examine the effect of internal governance, information asymmetry, and free cash flow on real earnings management, with managerial ownership serving as a moderating variable. The study employs a quantitative approach using secondary data obtained from the financial statements of consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The research sample consists of 28 firms selected through purposive sampling, resulting in 140 firm-year observations. Panel data regression analysis is applied using the Fixed Effect Model (FEM) and processed with EViews 13. The results indicate that internal governance and free cash flow have a significant effect on real earnings management, while information asymmetry does not exhibit a significant effect. Furthermore, managerial ownership does not moderate the relationship between internal governance and real earnings management. However, managerial ownership is found to strengthen the relationship between information asymmetry and real earnings management, as well as reinforce the effect of free cash flow on real earnings management. These findings suggest that managerial ownership plays a conditional role in influencing real earnings management practices. The study highlights the importance of strengthening internal governance mechanisms and enhancing financial reporting transparency to mitigate real earnings management and improve the quality of accounting information.